Hyperbolic Heat Conduction Equation - Zudin, Yuri B (Theory of Periodic Conjugate Heat Transfer, 2016)
In recent years considerable interest has been aroused to the problem of high-temperature heat conduction of solid-state body subject to strong high-frequency electronic and laser beams [1].